Transformasi Pemikiran Hukum Islam: Perbandingan Tokoh Klasik dan Kontemporer dalam Konteks Hukum Modern - Hendrayani (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2024)
Islamic legal thought undergoes dynamic development from the classical to the contemporary era, influenced by social, political, and cultural changes. This study aims to analyse and compare the Islamic legal thought of classical figures, such as Imam Abu Hanifah, Imam Malik, Imam al-Shafi'i, and Imam Ahmad bin Hanbal, with the thoughts of contemporary figures, such as Muhammad Abduh, Rashid Rida, Fazlur Rahman, and Abdullahi Ahmed An-Na'im, in facing modern legal challenges. This research uses a qualitative method with a historical-comparative approach to identify the transformation of Islamic legal thought and its relevance in contemporary legal practice. The results show that classical thought is more oriented towards sharia texts with a systematic methodology of legal istinbath based on ijma', qiyas, and istihsan, while contemporary thought emphasises the reinterpretation of Islamic law through ijtihad, maqasid sharia, and contextualisation of legal norms to remain relevant in modern social dynamics. This study contributes to providing a more comprehensive perspective on the evolution of Islamic law and its implications for the formation of Islamic legal policies in the modern era.